2022
DOI: 10.1002/bmc.5568
|View full text |Cite
|
Sign up to set email alerts
|

A combined qualitative and quantitative method development and validation of vancomycin hydrochloride injection formulation by HPLC and UV involving quality by design

Abstract: A selective, specific, precise, linear, accurate and robust analytical method was developed and validated for the assay of vancomycin HCl in vancomycin hydrochloride injection. Comparative UV spectrophotometric and reverse‐phase HPLC were used to develop the quantitative determination. Acetonitrile and pH 2.2 phosphate buffer in the ratio 20:80 v/v were used as the mobile phase, and a flow rate of 1.0 ml/min with a 20 min run time. The detection was carried out at 235 nm with a Nucleosil C18 (250 × 4.6 mm) 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The acid and alkali stress samples were neutralized with 5 m NaOH solution, and 5 m HCl solution, respectively. The oxidation sample solution was exposed to heat at 60°C for 3 min in a water bath to stop the chemical reaction (Gulshan et al, 2008; Jythesh, Koteswara Rao, et al, 2023; Mahesh et al, 2022; Narasimha et al, 2019; Nikita & Charmy, 2013; Sasikala et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The acid and alkali stress samples were neutralized with 5 m NaOH solution, and 5 m HCl solution, respectively. The oxidation sample solution was exposed to heat at 60°C for 3 min in a water bath to stop the chemical reaction (Gulshan et al, 2008; Jythesh, Koteswara Rao, et al, 2023; Mahesh et al, 2022; Narasimha et al, 2019; Nikita & Charmy, 2013; Sasikala et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Considering the sensitivity and toxicity of this impurity (its consumption of high levels will cause cancer), we have selected the RP-HPLC-MS/MS technique for the estimation of 2-amino-4-chlorophenol in ppm level (Figure 1) [19][20][21][22][23]. Both methods were developed and validated considering the International Council for Harmonization (ICH) requirements, which met its acceptance criteria and were found to be specific, linear, accurate, precise, and robust [24][25][26][27][28]. The results of the forced degradation study confirmed that the developed RP-HPLC-UV method is stabilityindicating, in addition to being specific and selective in the separation and quantitative determination of organicrelated impurities of chlorzoxazone drug substance and drug product [29,30].…”
Section: Introductionmentioning
confidence: 99%